A RNAi-based therapeutic proof of concept targets salmonid whirling disease in vivo. - Subhodeep Sarker; Simon Menanteau-Ledouble; Mohamed H Kotob; Mansour El-Matbouli (PLoS ONE)
Myxobolus cerebralis is a cnidarian-myxozoan parasite that causes salmonid whirling disease. M. cerebralis alternates between two hosts: (1) a vertebrate salmonid and (2) an invertebrate oligochaete, Tubifex tubifex. There is no successful treatment for salmonid whirling disease. MyxSP-1 is a M. cerebralis serine protease implicated in whirling disease pathogenesis. We hypothesized that short-interfering RNA (siRNA)-induced RNA interference (RNAi) can silence MyxSP-1 in the invertebrate host and abrogate the M. cerebralis life cycle. This would preclude whirling disease infection in the salmonid host. To test this hypothesis, we first developed a siRNA delivery protocol in T. tubifex. Second, we determined the effective dose for siRNA treatment of M. cerebralis-infected T. tubifex. M. cerebralis-infected T. tubifex were treated with different concentrations of MyxSP-1 or negative control siRNAs (1μM, 2μM, 5μM or 7μM) at 15°C for 24h, 48h, 72h and 96h, respectively. We monitored MyxSP-1 knockdown using real-time quantitative PCR (qPCR). siRNA treatment with MyxSP-1 siRNA at 2μM concentration for 24h at 15°C showed maximum significant MyxSP-1 knockdown in T. tubifex. Third, we determined the time points in the M. cerebralis life cycle in T. tubifex at which siRNA treatment was most effective. M. cerebralis-infected T. tubifex were treated with MyxSP-1 or negative control siRNAs (2μM concentration for 24h at 15°C) at 24 hours post-infection (24hpi), 48hpi, 72hpi, 96hpi, 1 month post-infection (1mpi), 2mpi and 3mpi, respectively. We observed that siRNA treatment of T. tubifex was most effective at 1mpi, 2mpi and 3mpi. Fourth, we immersed specific-pathogen-free rainbow trout fry in water inhabited by MyxSP-1 siRNA-treated T. tubifex (at 1mpi, 2mpi and 3mpi). The salmonids did not develop whirling disease and showed significant MyxSP-1 knockdown. We also observed long-term RNAi in T. tubifex. Together these results demonstrate a novel RNAi-based therapeutic proof of concept in vivo against salmonid whirling disease.